\(Schisandra grandiflora\) (Wall.) Hook. F. & Thomson (Schisandraceae: sect. \(Pleiostema\)), a new record for the flora of Vietnam - The Cuong, Nguyen; Van Hai, Do; Thi Hoan, Duong (Academia Journal of Biology, 2022)
Schisandra grandiflora (Wall.) Hook. f. & Thomson (Schisandraceae: sect. Pleiostema), the specimens collected in Ha Giang, Cao Bang, and Vinh Phuc provinces, as a new recorded species for the flora of Vietnam. A morphological comparison with related species and a key to species in Vietnam was provided. A description including details of distribution and habitat is supplied with a line-drawing.